Product Development with Analysing Customer Require ments and Techniques - Shalaka H. Joshi; Dr. G. M. Kakandikar (International Journal of Innovations in Engineering Research and Technology, 2021)
Every rewarding company has always used data and information to serve in its delineation procedure. In design a new product, engineers have always scrutinize the manufacturing and achievement history of the current product. The buyer Futures scenarios present plausible future developme nts, exploring the challenges and opportunities the consumer goods industry may face in 2020. We base all our scenarios on a set of certainties and uncertainties. This allows us to explore the way powerful trends may play out and interact to shape our future. Customer needs and wants are sensitive and complex. Through customer needs a nd competitive analysis, product development methods help to identify the critical technical com ponents that require change. FAST diagram represents a very powerful tool in analyzing complex sys tems and boiling down the descriptions of the functions performed into the essence of the task that must be delivered.